Powstanie i działalność Narodowej Partii Robotniczej-Lewicy w Łodzi w latach 1926–1932 - Kubiak, Jarosław (Acta Universitatis Lodziensis. Folia Historica, 2014)
NWP-Left was created in Łódź in autumn 1926 as a result of the secession of the National Workers Party activists supporting the government of marshal Józef Piłsudski. Throughout the period of his activity was the leftist wing of holding power in Poland the political camp known as „Sanation” movement in the 1926–1939 years. Initially party retained its organizational independence, but in 1930 was transformed into autonomous structure within the pro-government Nonpartisan Bloc for Cooperation with the Government. Numerous internal conflicts between different factions within the party about the direction of political activity and its role in the political scene of the country caused organizational crisis and decrease of popularity among residents of Łódź. As part of the process of looking for a new political identity NWP-Left has made changes of the program to a more left-wing course and the transformation into the National Labour Party in 1932.